Parallel Preference Structures in Labor Supply and Commodity Demand: An Adaptation of the Gorman Polar Form - Dickson, Jonathan G. (Econometrica, 1980)
This paper discusses the properties of parallel preference structures and their potential usefulness in empirical research. The parallel structure can accommodate arbitrarily flexible substitution properties and linear or nonlinear income-consumption curves, with the linear form representing a special case of the Gorman polar form. The global properties are distinctive in that indifference loci are parallel surfaces, identical in shape and scale at all utility levels. These properties are potentially appropriate for models of family labor supply but are less suitable for applications to production over a wide range of output. Alternative parameterizations and estimation forms are discussed and the model is shown to provide a basis for interpretation of models of labor supply estimated by Professors Ashenfelter and Heckman. PARALLEL PREFERENCE STRUCTURES are characterized by indifference surfaces that are identical in shape and scale, each being a translation of a basic surface along parallel income-consumption curves. The purpose of this paper is to discuss the properties of parallel structures and their potential usefulness in models of labor supply and commodity demand. Limited applications in production analysis are also discussed but are not the primary focus of the paper. In their most tractable form, with linear income-consumption curves, parallel 2 structures are a special case of the Gorman polar form. A suitably parameterized cost or expenditure function for a linear parallel structure provides a second order point approximation to an arbitrary general cost or expenditure function. By that criterion, a variety of simple versions of the parallel structure are on roughly equal footing with other flexible functional forms employed in recent demand, produc